2011
DOI: 10.1111/j.1469-8137.2011.03652.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of activities of root phosphomonoesterase and phosphodiesterase in wetland plants as a function of macrophyte species and ambient phosphorus regime

Abstract: Summary• Phosphorus (P)-limited plants produce higher amounts of root phosphatases, but research has mostly focused on phosphomonoesterases (PMEs). Because phosphate diesters can form a significant proportion of organic P in wetlands, we aimed to determine whether wetland plants produce both root PMEs and root phosphodiesterases (PDEs), and, if so, what factors influence activities of these enzymes.• We measured the activities of root PMEs and PDEs colorimetrically in a wide range of macrophytes from natural a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…and the lichen Cladonia portentosa (Dufour) Coem. indicates that PDE activity is five to ten times lower than PME activity (Asmar and GisselNielsen 1997;Chen et al 2002;Hogan et al 2010), but a recent study with various wetland plants in Belize showed that the difference between PME and PDE activity can be smaller than that (Rejmánková et al 2011). Also the role that mycorrhizae might play in PME activity for legumes and other plants under various soil N and P conditions is worth investigating.…”
Section: Discussionmentioning
confidence: 94%
“…and the lichen Cladonia portentosa (Dufour) Coem. indicates that PDE activity is five to ten times lower than PME activity (Asmar and GisselNielsen 1997;Chen et al 2002;Hogan et al 2010), but a recent study with various wetland plants in Belize showed that the difference between PME and PDE activity can be smaller than that (Rejmánková et al 2011). Also the role that mycorrhizae might play in PME activity for legumes and other plants under various soil N and P conditions is worth investigating.…”
Section: Discussionmentioning
confidence: 94%
“…The enzymatic activities in natural ecosystems are several orders of magnitude lower than in Pant et al's enzymatic assay. Nevertheless, relatively effective DOP retention has indeed been observed in periphyton and cattail dominated cells (Gu and Dreschel, 2008;Piccone et al, 2013) and especially P limitation may lead to increased utilization of DOP (Kuhn et al, 2002;Newman et al, 2003) which can be observed in increased activity of phosphatase and diesterase (Newman et al, 2003;Rejmánková et al, 2011). Our measurement of the enzymatic activity does also show some tendencies to an increased enzymatic activity from the inflow to the outflow in wetlands were the SRP concentration is low e.g.…”
Section: Orthophosphate Diesters and Their Degradation Productsmentioning
confidence: 96%
“…However, despite different classification schemes and terminologies there is no single commonly accepted functional type classification useful for all studies whether they are concerned with wetland or terrestrial plants (Sieben et al 2010). It seems that plant functional groups are being de novo defined for each individual study depending on the study aims (Rejmánková et al 2011).…”
Section: Introductionmentioning
confidence: 99%